Cozees, the self-heating blanket / Nur Anis Soffiya Suffian … [et al.] - Suffian, Nur Anis Soffiya; Zulkefli, Dafyna Qaisara; Mohmad Zaha, Nur Aliya; Mohd Yuzairy, Nurul Qhalisya Aleeya; Ahmad Fazli, Ahmad Afif Farhan; Muhammad Hanapiah, Zulkefli (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The "Cozees," a pioneering self-heating blanket targeting menstrual discomfort among individuals with disabilities and women. Amidst the absence of effective, portable solutions, Cozees integrates advanced heating tech into its fabric, providing tailored warmth for pain relief. Its adaptable settings cater to personalized comfort, complemented by breathable fabric for enhanced relaxation. Cozees discreetly addresses menstrual pain, empowering users to engage in daily routines comfortably. With its innovative approach and potential for customization, Cozees holds promise for commercialization, appealing to healthcare providers, retailers, and online platforms. By revolutionizing comfort and vitality, Cozees emerges as the quintessential solution for menstrual pain relief.